6.8k views
9 votes
If you were going to solve -3(x + 5) = 27, what is the first step that you would do? Why did you start there?

User Aioros
by
5.9k points

1 Answer

6 votes

Answer:

Explanation:

Multiply -3 for x and for 5

-3x-15=27

When you have this type of equation the first thing you do is take off the parentesis

Then you pass the 15 to the other side and you get -3x= 27 +15 . After that you divide that for -3 and you get the x . In this case x= -14

Sorry if the english is bad, i hope this helps

User Marievi
by
6.2k points